Substitute <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and find the result for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Simplify each term.

Subtract <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> from <math><mstyle displaystyle="true"><mo>-</mo><mn>2</mn></mstyle></math> .

Rewrite the expression using the negative exponent rule <math><mstyle displaystyle="true"><msup><mrow><mi>b</mi></mrow><mrow><mo>-</mo><mi>n</mi></mrow></msup><mo>=</mo><mfrac><mrow><mn>1</mn></mrow><mrow><msup><mrow><mi>b</mi></mrow><mrow><mi>n</mi></mrow></msup></mrow></mfrac></mstyle></math> .

Raise <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>7</mn></mstyle></math> .

Simplify the expression.

Write <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> as a fraction with a common denominator.

Combine the numerators over the common denominator.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>2187</mn></mstyle></math> .

Substitute <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and find the result for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Simplify each term.

Subtract <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> from <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Rewrite the expression using the negative exponent rule <math><mstyle displaystyle="true"><msup><mrow><mi>b</mi></mrow><mrow><mo>-</mo><mi>n</mi></mrow></msup><mo>=</mo><mfrac><mrow><mn>1</mn></mrow><mrow><msup><mrow><mi>b</mi></mrow><mrow><mi>n</mi></mrow></msup></mrow></mfrac></mstyle></math> .

Raise <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Simplify the expression.

Write <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> as a fraction with a common denominator.

Combine the numerators over the common denominator.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>729</mn></mstyle></math> .

Substitute <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and find the result for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Simplify each term.

Subtract <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Rewrite the expression using the negative exponent rule <math><mstyle displaystyle="true"><msup><mrow><mi>b</mi></mrow><mrow><mo>-</mo><mi>n</mi></mrow></msup><mo>=</mo><mfrac><mrow><mn>1</mn></mrow><mrow><msup><mrow><mi>b</mi></mrow><mrow><mi>n</mi></mrow></msup></mrow></mfrac></mstyle></math> .

Raise <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Simplify the expression.

Write <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> as a fraction with a common denominator.

Combine the numerators over the common denominator.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>243</mn></mstyle></math> .

Substitute <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and find the result for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Simplify each term.

Subtract <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Raise <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

Simplify the expression.

Combine the numerators over the common denominator.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>81</mn></mstyle></math> .

Substitute <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and find the result for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Simplify each term.

Subtract <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Raise <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> to the power of <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Simplify the expression.

Combine the numerators over the common denominator.

Add <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>27</mn></mstyle></math> .

This is a table of possible values to use when graphing the equation.

Do you know how to Graph Using a Table of Values f(x)=-3^(x-5)+1? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.